Transforming marine engineering education through Industry 4.0 integration and sustainability-driven curriculum design - Natanael Suranta; Marihot Simanjuntak; Panderaja Soritua Sijabat (Universitas Muhammadiyah Malang, 2025)
The maritime sector rapidly evolves due to technological innovations and growing environmental demands, necessitating a transformative shift in marine engineering education. Current curricula often fail to address these changes, particularly in incorporating Industry 4.0 technologies and sustainability principles. This study proposes a forward-looking curriculum framework that integrates digital innovations and green engineering practices to better align educational outcomes with industry needs. Adopting a qualitative approach, the research collected data through semi-structured interviews with maritime professionals, educators, and recent graduates. Descriptive analysis focused on key indicators such as technology integration, curriculum relevance, sustainability content, academia-industry collaboration, and educator development. The results highlight notable progress in embedding advanced technologies and environmental considerations into educational programs, with effectiveness strongly linked to institutional partnerships and continuous professional training for instructors. The study identifies gaps in applied skill readiness and sustainability practice but underscores the potential of collaborative curriculum design to close these gaps. Practical recommendations are offered to support the development of a future-ready workforce equipped to lead in a high-tech, environmentally responsible maritime industry. This research contributes to ongoing efforts to modernize marine engineering education and align it with global standards and emerging industrial demands.